Reflections on sociology of sport : ten questions, ten scholars, ten perspectives - Young, Kevin, 1959- (Bingley, U.K. : Emerald Publishing Limited, 2017)
In this tenth and celebratory volume in the Research in the Sociology of Sport series, ten recognized and influential sport scholars from around the world reflect on their respective academic journeys. They each address ten salient questions summarizing their career and their view of the current and future status of the sociology of sport. Each chapter addresses four main themes: About the author: who are your mentors and influential figures? What is your research trajectory? About sport: why does sport matter? How should sport be studied? Is sport a panacea for social problems? About practising sociology of sport: is teaching sociology of sport easy? Do sociologists like sport? Is the sociologist of sport a'public intellectual? About sociology of sport in the academy: does sociology of sport face institutional or industry barriers? What is the future of the sociology of sport? While the ten questions are salient for everyone in the academy irrespective of field of study, they seem particularly trenchant for sociologists of sport as the subfield reaches a chronological milestone and continues to undergo its own'growing pains' and maturation. Following quickly on the heels of, and conceptually tied to, Volume 9 (Sociology of Sport: A Global Subdiscipline in Review), Volume 10 now completes the'double celebration' of this book series as the sociology of sport subfield turns 50.
Prelims -- Stories from an academic life: reflections on being/doing/thinking/teaching in sociology of sport -- The sociology of sport in service of humanity -- The sociology of sport as a career and academic discipline -- Navigating'In-Betweenness' in studying sport in society -- Personal reflections on the past, present and future of sociology of sport -- Why studying sport matters: one woman's perspective as a sport sociology scholar -- My journey: personal reflections on a sociological craft -- Caribbean sport sociology: the ongoing journey -- The sociology of the taste for sociology of sport -- Approaching sport from historical and sociological perspectives: the life and work of a feminist scholar -- Index.
Includes index.
Includes bibliographical references.
Keywords: Sports -- Sociological aspects